Finding Obstacles to Growth: Is Infrastructure a Binding Constraint on African Light-manufacturing Firms? - Reppen, Stefan (International Journal of Economics and Financial Issues, 2015)
For African countries to develop and reduce poverty, it is necessary to create productive jobs and industrialise – which can happen through the light manufacturing sector. For such firms to grow, however, a good business environment is necessary. Thus, this paper analyses whether infrastructure puts a binding constraint on light-manufacturing firms in 8 African countries, and thus comprise a real bottleneck for development. The results indicate that there indeed exists a real bottleneck because of insufficient infrastructure for light manufacturing firms in general. However, there does not seem to be any significant difference between different sub sectors within the light-manufacturing sector. These findings indicate that, even at current levels of productivity, a relaxation of the constraints (i.e. improvements in the infrastructure supply) would significantly increase the economic activity, even without improvements in other areas of the business environment. Keywords: light manufacturing; Africa; infrastructure JEL Classifications: L6; O14